INFLUENCE OF AIRCRAFT TYPE AND ORDER ON FUEL SAVINGS GAINED BY TWO AIRCRAFT FORMATIONS - Marks, Tobias; Gollnick, Volker (2016)
The work presented in this paper investigates the influence of aircraft pairing and order on the fuel savings gained by two-aircraft formations. It will be analyzed if in terms of formation efficiency as well as with respect to the maximum fuel savings favorable aircraft pairings exist. To achieve this goal, a detailed trajectory analysis including an aerodynamic model to calculate the aerodynamic benefits of the formation is performed for a predefined set of formation geometries and formation pairings thus creating a formation flight database that can be used for the evaluation. It will be shown by statistical analysis, that differences in formation flight performance exist depending on pairing and order. In addition to the full initial set of samples a subset of the formation geometries representing missions over the North Atlantic will be evaluated. It will be shown, that differences compared to the full set of samples exist. As the weight of the leader is a strong driver for the formation efficiency it will be analyzed, if the take-off weights of the formation members allow an estimation of the achievable benefits. Furthermore it will be shown, how the database can be used to create surrogate models for a specific formation pairing and how these models can be utilized to evaluate specific formation geometries.